Is a Central Sediment Sample Sufficient? Exploring Spatial and Temporal Microbial Diversity in a Small Lake - Barbara Weisbrod; Susanna A. Wood; Konstanze Steiner; Ruby Whyte-Wilding; Jonathan Puddick; Olivier Laroche; Daniel R. Dietrich (Toxins, 2020)
(1) Background: Paleolimnological studies use sediment cores to explore long-term changes in lake ecology, including occurrences of harmful cyanobacterial blooms. Most studies are based on single cores, assuming this is representative of the whole lake, but data on small-scale spatial variability of microbial communities in lake sediment are scarce. (2) Methods: Surface sediments (top 0.5 cm) from 12 sites (n = 36) and two sediment cores were collected in Lake Rotorua (New Zealand). Bacterial community (16S rRNA metabarcoding), Microcystis specific 16S rRNA, microcystin synthetase gene E (mcyE) and microcystins (MCs) were assessed. Radionuclide measurements (210Pb, 137Cs) were used to date sediments. (3) Results: Bacterial community, based on relative abundances, differed significantly between surface sediment sites (p < 0.001) but the majority of bacterial amplicon sequence variants (88.8%) were shared. Despite intense MC producing Microcystis blooms in the past, no Microcystis specific 16S rRNA, mcyE and MCs were found in surface sediments but occurred deeper in sediment cores (approximately 1950′s). 210Pb measurements showed a disturbed profile, similar to patterns previously observed, as a result of earthquakes. (4) Conclusions: A single sediment core can capture dominant microbial communities. Toxin producing Microcystis blooms are a recent phenomenon in Lake Rotorua. We posit that the absence of Microcystis from the surface sediments is a consequence of the Kaikoura earthquake two years prior to our sampling.